Investigation of antimicrobial activity and morphological properties of metal coated textile surfaces - Necdet Aslan; Kenan Şentürk; Tuba Şen; Turgay Çoruhlu; İpek Vartürk; Şeker, S; Shahidi, S.; Dobrovolskiy, A.M.; Tsiolko, V.V.; Matsevich, S.V.; Keskin, S.S.; May Korachi (Вопросы атомной науки и техники, 2014)
The results of investigation antimicrobial and surface properties of the textiles metal coated by means of magnetron or the cleaning-deposition system, which is based on sequentially arranged DC anode layer accelerator and hollow cathode, are presented. The antimicrobial properties against bacteria E. coli and S. aureus of cotton and polyester/cotton textiles coated by Cu, Ti and Ag with the use of two different systems were examined and compared.